The major biogenic amine metabolites in mood disorders - Yang, Jingyi; Yuan, Minlan; Zhang, Wei (Frontiers in Psychiatry, 2024)
Mood disorders, including major depressive disorder and bipolar disorder, have a profound impact on more than 300 million people worldwide. It has been demonstrated mood disorders were closely associated with deviations in biogenic amine metabolites, which are involved in numerous critical physiological processes. The peripheral and central alteration of biogenic amine metabolites in patients may be one of the potential pathogeneses of mood disorders. This review provides a concise overview of the latest research on biogenic amine metabolites in mood disorders, such as histamine, kynurenine, and creatine. Further studies need larger sample sizes and multi-center collaboration. Investigating the changes of biogenic amine metabolites in mood disorders can provide biological foundation for diagnosis, offer guidance for more potent treatments, and aid in elucidating the biological mechanisms underlying mood disorders.